Rectify. The complete second season [videorecording (DVD)] - Young, Aden; Spencer, Abigail, 1981-; Clemens, Adelaide, 1989- (Anchor Bay Entertainment, 2015)
Daniel Holden is committed to living in the present. Unfortunately, there are many places and faces in his hometown that remind Daniel of the past; his incarceration, Hanna, and his role in Hanna's murder.